A novel quantitative assay of mitophagy: Combining high content fluorescence microscopy and mitochondrial DNA load to quantify mitophagy and identify novel pharmacological tools against pathogenic heteroplasmic mtDNA. (October 2015) - Diot, Alan; Hinks-Roberts, Alex; Lodge, Tiffany; Liao, Chunyan; Dombi, Eszter; Morten, Karl; Brady, Stefen; Fratter, Carl; Carver, Janet; Muir, Rebecca; Davis, Ryan; Green, Charlotte J; et al.
Graphical abstract: Abstract: Mitophagy is a cellular mechanism for the recycling of mitochondrial fragments. This process is able to improve mitochondrial DNA (mtDNA) quality in heteroplasmic mtDNA disease, in which mutant mtDNA co-exists with normal mtDNA. In disorders where the load of mutant mtDNA determines disease severity it is likely to be an important determinant of disease progression. Measuring mitophagy is technically demanding. We used pharmacological modulators of autophagy to validate two techniques for quantifying mitophagy. First we used the IN Cell 1000 analyzer to quantify mitochondrial co-localisation with LC3-II positive autophagosomes. Unlike conventional fluorescence and electron microscopy, this high-throughput system is sufficiently sensitive to detect transient low frequency autophagosomes. Secondly, because mitophagy preferentially removes pathogenic heteroplasmic mtDNA mutants, we developed a heteroplasmy assay based on loss of m.3243A > G mtDNA, during culture conditions requiring oxidative metabolism ("energetic stress"). The effects of the pharmacological modulators on these two measures were consistent, confirming that the high throughput imaging output (autophagosomes co-localising with mitochondria) reflects mitochondrial quality control. To further validate these methods, we performed a more detailed study using metformin, the most commonly prescribed antidiabetic drug that is still sometimes used in Maternally Inherited Diabetes and Deafness (MIDD). This confirmed our initial findings and revealed that metformin inhibits mitophagy at clinically relevant concentrations, suggesting that it may have novel therapeutic uses.